Tourism by the Sea. Development of Customs, Habits and Fashion on the Beach - Kavrečič, Petra (ZoneModa Journal, 2021)
The paper studies the development of seaside tourism, presenting the phases of its development: from health resorts, swimming in the cold sea, and slowly moving towards the warmer southern seaside destinations. It touches upon the initiators and promotors of medical treatments with sea air and bathing. It also focuses on customs and fashion on the beach. In order to understand the evolution of the bathing suits, the processes and circumstances, which influenced the development of customs, regulations on the beach and fashion, will be presented. How did the “evolution” of the bathing or swimsuit take place during the 19th and 20th century? It is important to understand when and why the previously “dangerous” and unfriendly sea has acquired healing characteristics and what were the factors and dynamics that encouraged the fashion of bathing in seawater. The aim is to present how the rituals on the beach evolved and how the life on the beach changed throughout time and became one of the most spread and popular leisure activity in summer.